Gestión de la calidad con base a las normas iso de la Cooperativa de Ahorro y crédito San José Ltda, provincia de los Rios, cantón Montalvo, período 2011-2012 - Ibarra Zúñiga, Amada Raquel (2012)
The present research was based on ISO 9000, which includes the implementation of quality systems in the enterprise, system maintenance and performance of the functions of quality in organizations that are interested in implementing the standards for better administration. In the study conducted in this research process was the importance of implementing the ISO in the Cooperative as well as having a clear understanding of the processes that must be run to avoid dissatisfaction among partners at the point of service delivery. We have developed the theoretical framework that is based on everything related to the origin of the ISO, management, monitoring and evaluation thereof and quality management issues as well as quality principles, application of ISO standards operational office. This thesis is structured in accordance with regulations issued by the State University of Bolivar, which contains three chapters, in the first chapter consists of the subject, background, problem statement, justification, overall objective and specific, theoretical framework, conceptual and scientific , in the second chapter analyzes and interpretation of results, and in the third chapter of the proposal which includes the Quality Management Manual applied to the administrative process of the Savings and Credit Cooperative San José Ltd. For the research instruments used for data collection as survey applied to officials of the Cooperative and interview the Manager for real data which allowed to detect the fundamental aspects for the development and preparation of the thesis also served to draw the conclusions and recommendations that facilitate clear and concrete to find alternative solutions to the problem. XVI According to the results of the field research, all that information collected, tabulated and their respective analysis leads to develop a proposal for the Quality Manual. The manual is a document that will serve as a guide to improve the care of partners and achieve their needs.